Collaborative Ethnography With Social Movements: Key Dimensions and Challenges - Arribas Lozano, Alberto (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2022)
In this article, I explore collaborative ethnography as a means to bridge theory and practice, knowledge and action, in social movement research, and to produce knowledge that is relevant and useful both inside and outside academia. For this purpose, I will present a group of interconnected dimensions and challenges that shape the practice of research collaboration with social movements: a situated, artisanal and experimental ethos regarding method and outcomes; elements of shared authority, co-decision, co-analysis, and co-theorization in fieldwork; the decentered role of scholars; the tension between academic and extra-academic relevance; the link between trust, access, and collaboration; epistemic and methodological questions of writing and representation; the significance of time for weaving and sustaining collaboration; and the ways in which the actors involved relate to knowledge-practices and theory production. These eight dimensions illustrate how ethnographic collaboration takes place (or fails to materialize) in actual research projects, highlighting elements that will facilitate or hinder the co-production of knowledge with our co-researchers.